Exercise Habits, Hematogram and Blood Chemistry of Diabetes Mellitus Patients at Risk For Metabolic Syndrome, Bantul Public Health Center - Hidayati, Titiek; M Gugun, Adang; Akrom, (International Journal of Psychosocial Rehabilitation, 2020)
Exercise habits are one of the WHO recommendations as a form of non-pharmacological therapy in patients with DM. This study was conducted with a cross-sectional design in 99 patients at risk for DM. The mean of GDS, cholesterol, and triglyceride levels were subjected to a mean difference test with a one-way t-test with 95% significance. The results show that the majority of the research subjects are women, basic education, private employment, exercise habits, average blood cavern level and fasting higher than the target (257.88 ± 117.76 mg/dl), and triglyceride levels (204.66 ± 103.83 mg/dl). There are also Hb levels (12.95 ± 1.49), leukocyte count (8.96 ± 1.96), platelet counts (321.24 ± 0.74) and erythrocytes (4.53 ± 0.55). The cholesterol level of the test subject is also within the normal range (169.72 ± 39.23 mg/dl). The results show that the Hb and hematocrit levels of the exercise group are higher than the non-exercise group (p